Relationships of soil erodibility parameters and water quality indices along Tigris Riverbanks, Baghdad City, Iraq. Issue 1 (1st January 2021) - Adnan, Tamarah A.; Al-Madhhachi, Abdul-Sahib T.; Mohammed, Eman A.
Abstract: One of the most important causes of river pollution is soil and water pollutions since no previous numerical studies linked the water quality indices and soil erosion parameters. The current research investigates the relationships between water quality parameters and indices versus parameters of soil erodibility ( τc and kd ) of Tigris Riverbanks within Baghdad City, Iraq. Besides, the research aims to create a new Iraqi Water Quality Index (IWQI) based on 10 parameters of water quality and compare the results with the Canadian Water Quality Index (CWQI). Finally, the research explores the spatial distribution of soil erodibility and water quality parameters using spatial analysis tools to produce forecast maps for water parameters and soil erodibility parameters. Forty samples of water and 30 samples of soil were collected from the five sites in Baghdad city during the winter and summer of 2019–2020. The mini-JET (miniature version of Jet Erosion Test) instrument was used to derive the soil erodibility parameters ( τc and kd ) for the five selected sites. The results showed that CWQI for all study sites of Tigris Riverbanks could be classified as inferior during the two seasons, while the new IWQI classified the water as good quality. The results showed that there was a relationship between water quality indices and soil erodibility parameters of Tigris Riverbanks. A direct relationship of two indices CWQI and IWQI versus τc was observed during the winter season with R 2 of 0.86 for τc -CWQI and τc -IWQI. An inverse relationship between kd -CWQI and kd -IWQI with R 2 of 0.90 and 0.86 was observed during the winter season. Similar results were obtained for the summer season but with low correlations of water quality indices versus kd . This research concluded that as water quality was poor, the soil erodibility was high.